Strategi Humas di SMK IPIEMS Surabaya Dalam Meningkatkan Citra dan Kepercayaan Publik Pada Masa Pandemi Covid-19 - Puji Rahayu; Novi Trisnawati (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
The COVID-19 pandemic has had a major impact on the education sector. The implementation of distance learning (PJJ) has made students and parents worried about not getting a proper education. This is a separate obstacle for vocational schools that have to spend a lot of productive vocational learning with practice. In this case, Public Relations is required to create a new strategy to maintain its quality and competitiveness. This study aims to find out how the strategies and factors that support and hinder public relations in increasing a positive image and public trust during the COVID-19 pandemic. The method used in this research is descriptive qualitative. Data collection techniques with interviews, observation, and documentation. The results of the study show that the IPIEMS Vocational School's strategy in its success in increasing public image and trust during the COVID-19 pandemic is to meet all the needs and demands of the community for schools and actively publish through social media. The supporting factors are 1) harmonious and synergistic support from school principals and colleagues (wakasek and kaproli) in planning the implementation of public relations programs, 2) Loyalty of students and alumni in promoting schools, 3) Awareness of the important role of technology in education long before the COVID pandemic -19 . The inhibiting factor for achieving public relations goals is a common problem experienced by almost all schools.